Template Assisted Electrochemical Growth of Cobalt Nanowires: Influence of Deposition Conditions on Structural, Optical and Magnetic Properties - Casagrande-Denardin, J (2011)
The influence of electrodeposition potential, pH, composition and temperature of the electrolytic bath on the structure of cobalt nanowires arrays electrodeposited into anodic aluminum oxide (AAO) porous membranes is reported. XRD, SEM, and TEM analysis were employed to characterize structural (crystal phase, crystallographic texture, and grain size), and morphological nanowire properties. It was confirmed that at pH 2 the electrodeposition potential has not influence on the preferred crystallographic orientation of the electrochemically grown Co nanowires. At pH 4 the electrodeposition potential controls the growth of cobalt nanowires along some preferential crystallographic planes. The electrolytic pH bath modulates the fcc or hcp phase exhibited by the cobalt nanowires. Single crystalline nanowires with a hcp phase strongly oriented along the (2021) crystallographic plane were obtained at pH 4 and at-1.1 V (vs. Ag/AgCl), a result not previously reported. High electrolytic bath temperatures contributed to improve the single crystalline character of the cobalt nanowires. The presence of chloride anion in the electrolytic bath also influenced on the structural properties of the resulting cobalt nanowires, improving their crystallinity. The optical reflectance of the samples shows a structure in the UV-blue region that can be assigned to the two-dimensional morphology arising in the shape of the almost parallel nanowires. Magnetic measurements showed that different electrodeposition potentials and electrolytic bath pH lead to different magnetic anisotropies on the nanowire array samples. Copyright © 2011 American Scientific Publishers All rights reserved.